Bearing the Brunt: The Effect of Terrorism on the Foreign Direct Investment in South Asian Association for Regional Cooperation (SAARC) Nations - Mansoor, Abdul (University of Wah Journal of Social Sciences, 2022)
The current state of terrorism has posed serious challenges to macroeconomic environment stability by causing the dislodgment of foreign direct investment (FDI). This study aims to find the impact of terrorism along with other important policy variables such as FDI, Terrorism, law and order, Tariff, and Government regulation in the SAARC member nations, namely, Bangladesh, Bhutan, India, Nepal, Pakistan, Afghanistan, Maldives, and Sri Lanka. Utilizing a panel econometric estimation model on annual data from 1990-2019, the results of the study show a significant negative impact of terrorism and law and order situations in the SAARC countries. Whereas the magnitude of FDI is technology-driven in Pakistan, Bangladesh, and Afghanistan where there is a deep focus on the physical structural transformation. This empirically establishes the fact that terrorism is a serious threat to FDI and economic growth for the economies in this region.